SIFAT ARANG EMPAT JENIS BAMBU - Tjutju Nurhayati Syahri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
Studies on the properties of bamboo charcoal processed by destructive distillation has been conducted. Four different species of bamboo have been selected, i.e. andong (Gigantochloa vertivillata Munro), ater (G. ater Kurz), tali (G. apus Kusz), and bitung (Dendrocalamus asper Back), were obtained from Kabupaten Bogor. The properties of interest are: the specific gravity, calorific value, ash content, volatile matter, and the fixed carbon content on three different parts of bamboo trunk (bottom, middle, and top).The specific gravity and the properties of the destructive distillation products from each part of bamboo trunk were significantly different. The lowest part of bamboo trunk revealed the highest yield and the highest density of charcoal. In contrast, the yield of piroligneous ligour gave a tendency of decreasing toward the lowest part of bamboo trunk; exception was found in bamboo ater and tali, which indicated the highest content in the middle part of the trunk.All four different species of bamboo gave fairly the same yield of destructive distillation products. The average yield of charcoal, the content of piroligneous ligour , and the tar content were 36.05, 40.58, and 6,550'/o, respectively.The specific gravity of all four different charcoal were significantly different, the highest was found in ater charcoal (0. 6), and the lowest was in bitung (0.3). The highest ash content was found in bitung charcoal (7.50'/o), and the lowest was indicated by tali charcoal (5. 70'/o). The highest volatile matter was in tali charcoal (24.40'/o), and the lowest content was in bitung (/7.800'/o). The highest and the lowest fixed carbon content were found in bitung (75. 50'/o) and tali charcoal (69. 80'/o ), respectively.There were no great differences in calorific value for all different species of bamboo, with the average of 6602 ca/lg charcoal. However, different part of bamboo trunk indicated significantly different calorific value, that is, the higher the position in the trunk, the lower the calorific value.